Uma Abordagem metodológica para suporte da gestão dos resíduos de equipamentos eletroeletrônicos urbanos: aplicação ao caso do município de Fortaleza - Costa, Karla Alamar (2016)
Despite the enactment of Law 12,305, in August 2010, establishing the National Solid Waste (PNRS) policy, there are many Brazilian cities that still have their waste disposal without any control, causing serious environmental and public health consequences. In this context, the electrical and electronic equipment (WEEE) waste are necessarily defined as the Reverse Logistics objects, according to PNRS. These wastes are composed of toxic substances that pose a threat to the environment and to people handling them. It is observed also that international exchanges occur with such wastes without support of effective legislation. Furthermore, recycling of WEEE has economic advantages, since many of these wastes are made of valuable components. The present study proposes a management model for the subsector of urban eletrical/electronic equipment waste using the concepts of Systemic Analysis, Matriz GUT and Benchmarking in Reverse Logistics, utilizing as the case study the city of Fortaleza, in the Northeastern Brazil. It emphasises the shared responsibility of the actors involved. The work tries to contribute to a better comprehension of a quite economic, social and global significant area, since this field impacts the economy as well as nature, adding value and respecting the living creatures.